Nursing Care for Avascular Necrosis Patients After Total Hip Replacement Surgery: Case Report - Tanjung, Dudut; Yannis, Nafi; Edianto, Edianto; Afriani, Dina (Jurnal Keperawatan Priority, 2025)
Avascular Necrosis (ANV) is a pathological condition caused by impaired blood supply to the subchondral femur bone, causing necrosis and deformity of bone tissue. This condition causes severe pain, joint stiffness, and impaired physical mobility. Chronic avascular necrosis requires surgery to stabilize physical function. Total Hip Replacement surgery is one of the surgical options to relieve pain and restore joint function in patients with avascular necrosis. Nursing care for ANV patients is very important in managing pain, preventing complications, and promoting recovery. Through comprehensive nursing care, nurses have a significant impact on the physical and emotional health of patients, helping them live healthier and more functional lives. This article aims to implement nursing care for avascular necrosis patients undergoing surgery at Haji Adam Malik General Hospital, Medan. This study is a case report of a 63-year-old patient who had suffered from avascular necrosis for 10 years and underwent Total Hip Replacement surgery. Assessment data were collected through physical examination and supplemented with laboratory and radiology results. The postoperative diagnoses that are the priority in this patient are acute pain, impaired physical mobility, impaired skin integrity, and self-care deficit. Nurses focus on the criteria for treatment outcomes in reducing pain levels, increasing joint range of motion and physical mobility, improving skin integrity, and improving self-care. The intervention results are pain control that allows earlier mobilization and can be a reference for professional nurses in improving the quality of service, especially for avascular necrosis patients undergoing Total Hip Replacement (THR) surgery.